TECHNOLOGY OF PREVENTIVE MEASURES TO PREVENT VIOLENCE AMONG YOUTH - Ibragimov Shukhrat Isroilovich (Innovate Conferences, 2025)
The technology of preventive measures in the prevention of crime among young people is an effective approach aimed at developing legal culture in the social environment and reducing crime. This technology helps to prevent crime by providing young people with legal knowledge, conducting various educational programs, trainings, seminars and workshops with them. The technology of preventive measures serves to ensure security in society by combating bad habits and crime among young people, awakening and forming legal awareness in the social environment.
Keywords: prevention, education, national experience, international experience, social responsibility, society, approaches, effectiveness.